2008
DOI: 10.1128/aac.00813-07
|View full text |Cite
|
Sign up to set email alerts
|

Exposure-Response Analyses of Tigecycline Efficacy in Patients with Complicated Intra-Abdominal Infections

Abstract: Exposure-response analyses were performed to test the microbiological and clinical efficacies of tigecycline in complicated intra-abdominal infections where Escherichia coli and Bacteroides fragilis are the predominant pathogens. Data from evaluable patients enrolled in three clinical trials were pooled. Patients received intravenous tigecycline (100-mg loading dose followed by 50 mg every 12 h or 50-mg loading dose followed by 25 mg every 12 h). At the test-of-cure visit, microbiological and clinical response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
80
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 23 publications
(22 reference statements)
2
80
2
1
Order By: Relevance
“…However, the median fAUC 0 -24 / MIC ratios, 1.73 and 4.39 for subjects with VAP and with HAP, respectively, in this trial were lower than those observed in other tigecycline trials (14). The median AUC 0 -24 /MIC ratios in patients being treated for complicated intra-abdominal infections and complicated skin and skin structure infections were 15.6 (15) and 29.0 (24), respectively, which would correspond to fAUC 0 -24 / MIC ratios of 3.1 and 5.8, respectively, assuming an unbound fraction of 20%.…”
mentioning
confidence: 60%
“…However, the median fAUC 0 -24 / MIC ratios, 1.73 and 4.39 for subjects with VAP and with HAP, respectively, in this trial were lower than those observed in other tigecycline trials (14). The median AUC 0 -24 /MIC ratios in patients being treated for complicated intra-abdominal infections and complicated skin and skin structure infections were 15.6 (15) and 29.0 (24), respectively, which would correspond to fAUC 0 -24 / MIC ratios of 3.1 and 5.8, respectively, assuming an unbound fraction of 20%.…”
mentioning
confidence: 60%
“…With high susceptibilities demonstrated in surveillance studies (2) and positive clinical outcomes shown in trial data from subpopulations infected with ESBL-producing Enterobacteriaceae (6, 23), tigecycline has been increasingly utilized as a treatment option. Given these occurrences and the few available studies describing the exposure-response relationship for the treatment of gram-negative organisms (15,19,21), it seems reasonable to uncover the pharmacodynamics of tigecycline.Herein, we described the pharmacodynamic profile of tigecycline and the magnitude of its efficacy against a diverse group of E. coli and K. pneumoniae isolates in the mouse thigh model. …”
mentioning
confidence: 99%
“…During the course of its development, tigecycline has been the subject of several pharmacokinetic-pharmacodynamic (PK-PD) analyses, using data from animal infection models as well as data from clinical trials of patients suffering from complicated skin and skin structure infections or those with complicated intra-abdominal infections (3,4,8). These analyses have characterized the magnitude of the ratio of the area under the concentration-time curve at 24 h to the MIC of the pathogen (AUC 0-24 :MIC), the PK-PD measure most predictive of outcome, which is associated with efficacy.…”
mentioning
confidence: 99%